Modifications of Gait as Predictors of Natural Osteoarthritis Progression in STR/Ort Mice. Issue 7 (July 2014) - Poulet, Blandine; de Souza, Roberto; Knights, Chancie B.; Gentry, Clive; Wilson, Alan M.; Bevan, Stuart; Chang, Yu‐Mei; Pitsillides, Andrew A.
<x xml:space="preserve">Abstract</x> Objective Osteoarthritis (OA) is a common chronic disease for which disease‐modifying therapies are not currently available. Studies to seek new targets for slowing the progress of OA rely on mouse models, but these do not allow for longitudinal monitoring of disease development. This study was undertaken to determine whether gait can be used to measure disease severity in the STR/Ort mouse model of spontaneous OA and whether gait changes are related to OA joint pain. Methods Gait was monitored using a treadmill‐based video system. Correlations between OA severity and gait at 3 treadmill speeds were assessed in STR/Ort mice. Gait and pain behaviors of STR/Ort mice and control CBA mice were analyzed longitudinally, with monthly assessments. Results The best speed to identify paw area changes associated with OA severity in STR/Ort mice was found to be 17 cm · seconds−1. Paw area was modified with age in CBA and STR/Ort mice, but this began earlier in STR/Ort mice and correlated with the onset of OA at 20 weeks of age. In addition, task noncompliance appeared at 20 weeks. Surprisingly, STR/Ort mice did not show any signs of pain with OA development, even when treated with the opioid antagonist naloxone, but did exhibit normal pain behaviors in response to complete Freund's adjuvant–induced arthritis. Conclusion The present results identify an animal model in which OA severity and OA pain can be studied in isolation from one another. The findings suggest that paw area and treadmill noncompliance may be useful tools to longitudinally monitor nonpainful OA development in STR/Ort mice. This will help in providing a noninvasive means of assessing new therapies to slow the progression of OA.